2019
DOI: 10.18231/j.tjp.2019.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of psychosocial factors in attempted suicides attending a tertiary care hospital in Kanchipuram, South India

Abstract: Introduction: Suicide attempt is a self-injurious behavior with a non-fatal outcome. An insight into psychosocial factors and methods used can be used to device effective preventive strategies. Aims:The aim is to study the psycho-social factors and to find the frequency of different methods used in attempted suicides. Materials and Methods:This study is a descriptive, cross-sectional, hospital-based analysis of attempted suicides. 44 consecutive attempted suicides admitted in the emergency ward and referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…14 Another study reported the presence of psychiatric illness, substance use disorders, and severe medical illness (such as cancer, head injury, peptic ulcer disease, HIV/AIDS, and chronic pain) as some of the other factors that result in suicidal ideation. 15 Research suggests that suicide attempts tend to recur with each attempt showing increased capability of lethality and almost half of serious suicide attempters make another attempt within 5 years. 16 Addressing patient's distress, understanding their perspectives, provision of support, education, coping strategies, regular review, and follow-up might be helpful in forestalling reattempts.…”
Section: Introductionmentioning
confidence: 99%
“…14 Another study reported the presence of psychiatric illness, substance use disorders, and severe medical illness (such as cancer, head injury, peptic ulcer disease, HIV/AIDS, and chronic pain) as some of the other factors that result in suicidal ideation. 15 Research suggests that suicide attempts tend to recur with each attempt showing increased capability of lethality and almost half of serious suicide attempters make another attempt within 5 years. 16 Addressing patient's distress, understanding their perspectives, provision of support, education, coping strategies, regular review, and follow-up might be helpful in forestalling reattempts.…”
Section: Introductionmentioning
confidence: 99%